Problems of consistency of gas dynamic characteristics of centrifugal compressor sections and selection of anti-surge control valves - A. D. Vanyashov; I. A. Yanvarev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Options of approach to selection of standard size of anti-surge control valves in relation to two-section (two-shell) centrifugal compressor unit with three control circuits (first section, second section, general circuit) are considered. The problems arising from valve selection due to incorrect calculation of gas dynamic characteristics of compressor sections are shown. Field of application — natural and associated gas production and compression facilities.